Actein Inhibits Tumor Growth and Metastasis in HER2-Positive Breast Tumor Bearing Mice via Suppressing AKT/mTOR and Ras/Raf/MAPK Signaling Pathways - Wu, Xiao-Xiao; Yue, Grace Gar-Lee; Dong, Jin-Run; Lam, Christopher Wai-Kei; Wong, Chun-Kwok; Qiu, Ming-Hua; Lau, Clara Bik-San (Frontiers in Oncology, 2020)
HER2-positive breast cancer accounts for 15-20 % in breast cancer and 50 % of the metastatic HER2-positive breast cancer patients died of central nervous system progression. The present study investigated the effects of actein (a natural cycloartane triterpene) on cells adhesion, migration, proliferation and matrix degradation, and its underlying mechanism in HER2-positive breast cancer cells. The in vivo effect of actein on tumor growth and metastasis in MDA-MB-361 tumor-bearing mice as well as the anti-brain metastasis in tail vein injection mice model were also investigated. Our results showed that actein inhibited HER2-positive breast cancer cells viability, proliferation and migration. Actein also induced MDA-MB-361 cells G1 phase arrest and inhibited the expressions of cyclins and cyclin-dependent kinases. For intracellular mechanisms, actein inhibited the expressions of molecules in AKT/mTOR and Ras/Raf/MAPK signaling pathways. Furthermore, actein (15 mg/kg) was shown to exhibit anti-tumor and anti-metastatic activities in MDA-MB-361 breast tumor-bearing mice, and reduced brain metastasis in tail vein injection mice model. All these findings strongly suggested that actein is a potential anti-metastatic agent for HER2-positive breast cancer.